2001
DOI: 10.1021/np000630e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stereochemistry of Epoxyserratanes from the Cuticle of Picea jezoensis var. jezoensis

Abstract: Three new epoxytriterpenes, 14 beta,15 beta-epoxy-21 beta-hydroxyserratan-3-one (1), 13 alpha,14 alpha-epoxy-21 alpha-methoxyserratan-3-one (2), and 13 alpha,14 alpha-epoxy-3 beta-methoxyserratan-21 beta-ol (3), were isolated together with two known triterpenoids, 21 alpha-methoxyserrat-13-en-3-one (4) and 21 beta-hydroxyserrat-14-en-3-one (5), from the cuticle of Picea jezoensis var. jezoensis. The structures of these new compounds were established on the basis of spectral data (NMR, MS) and single-crystal X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Compound 1 is a serratane-type pentacyclic triterpene ketone with 4 secondary alcohols, a tertiary alcohol and 2 oxymethlenes. The 1 H-and 13 C-NMR chemical shift values of 1 were similar to those reported in the literature [14,15], apart from that the most characteristic signal peak of C-27 (δ C ≅ 56.0) which was absent from the spectra (see l " Table 1) [16,17]. We therefore concluded that the methylene group at C-27 of serratane was oxidized to a methine group.…”
Section: Supporting Informationsupporting
confidence: 85%
“…Compound 1 is a serratane-type pentacyclic triterpene ketone with 4 secondary alcohols, a tertiary alcohol and 2 oxymethlenes. The 1 H-and 13 C-NMR chemical shift values of 1 were similar to those reported in the literature [14,15], apart from that the most characteristic signal peak of C-27 (δ C ≅ 56.0) which was absent from the spectra (see l " Table 1) [16,17]. We therefore concluded that the methylene group at C-27 of serratane was oxidized to a methine group.…”
Section: Supporting Informationsupporting
confidence: 85%
“…In the NOESY spectrum of 2 (Fig. 1) , and the fragment pattern was close to that of 3 [7]. All these data indicated that the structure of 2 as 13b,14b-epoxy-3b-methoxyserratan-21b-ol, which was confirmed by synthesis.…”
Section: Structure Determination Of 1 Andsupporting
confidence: 55%
“…jezoensis (Japanese name: Ezomatsu) (Pinaceae) was selected for detailed investigation. In previous papers, we had reported a considerable number of serratane-type triterpenenoids from this stem bark [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 90%
“…240 The serratane epoxides 330, 331 and 332 have been isolated from Picea jezoensis var., jezoensis. 241 The structures of 330 and 331 were confirmed by X-ray analysis. Adiantutirucallene B 333 and adiantulanostene B 334 are strange triterpenoids from Adiantum venustrum.…”
Section: Miscellaneous Compoundsmentioning
confidence: 82%